UPAYA MENINGKATKAN MOTIVASI BELAJAR SISWA PADA MATERI KEBUTUHAN DASAR MANUSIA DENGAN MODEL PEMBELAJARAN DISCOVERY LEARNING DI SMAN I TUKKA - Manullang, Herlina (Ndrumi : Jurnal Ilmu Pendidikan dan Humaniora, 2024)
This study aims to investigate the learning motivation of students by applying the Discovery Learning model in class X1-IPS 2 at SMA Negeri 1 Tukka and to evaluate its enhancement. The research target is 25 students of grade XI IPS-2 at SMA Negeri 1 Tukka. The method employed is Classroom Action Research (CAR), comprising 2 cycles with 3 meetings each. Evaluation is conducted at the final meeting of each cycle. Results indicate an increase in student learning motivation from 40.67 before using Discovery Learning to 63.267 in cycle I and 75.33 in cycle II, with an increase of 13.79%. Student activity observation also shows improvement, from 60.14% to 68.88% in cycle I, and from 70.83% to 89.27% in cycle II, categorized as "very active". These findings indicate the effectiveness of the Discovery Learning model in enhancing students’ learning motivation and engagement in the geography learning process.